Simulação de aquecimento de fluidos em dutos de petróleo usando ondas eletromagnéticas - Andrade Neto, José Dias de (2016)
With the increasing demand of oil products, the need arises to seek more and more new extraction techniques to increase the production of barrels at the lowest possible cost. With this also comes the concern for the environment and the entire ecosystem near the mining fields. Techniques to increase the recovery factor of these wells has been developed and refined over the past few years. The heating method by microwave is a process where the electromagnetic energy at high frequency is transformed into thermal energy dielectric loss and / or electromagnetic absorption. Research using as a basis the increase of technical electromagnetic heating recovery factor is still poorly developed. The present work aim is to develop a pipeline model filled by brackish water and heavy oil, the main components present in oil wells the Northeast, and heating it using microwaves to reduce its viscosity. This process is intended to prevent the extraction system is blocked by paraffin buildup. Five models were developed for the realization of studies heating by electromagnetic radiation and potential were varied in three steps. The simulations were all developed using multifísico software COMSOL. The simulation results are plotted in graphs in one and two dimensions, in order to compare the performance of each model used to describe the energy conversion efficiency in the system and analyzing the propagation and absorption of electromagnetic radiation in the dielectric